2005
DOI: 10.1515/text.2005.25.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Modern Conscience: Modalities of Obligation in Research Genres

Abstract: Despite growing evidence of its social and rhetorical aspects, research writing still has a reputation for impersonal neutrality and 'facelessness'. This study revisits that neutrality by investigating expression of moral obligation-deontic modals and related expressions-in 105 research articles in three disciplines: Forestry, Social Psychology, Urban Geography. In all three disciplines, deontics express obligation to pursue knowledge, these expressions composing disciplined cohorts of researchers. In all thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 4 publications
0
17
0
3
Order By: Relevance
“…For example, Hyland (2005b) examined interactional metadiscourse in 240 RAs from eight disciplines straddling the hard/soft division and reported that RAs from the soft disciplines used interactional metadiscourse more frequently than RAs from the hard disciplines. Differences between hard and soft disciplines were also reported for specific types of interactional resources: hedges (Abdi, 2002;Hyland, 1998Hyland, , 2005bVold, 2006), boosters (Hyland, 1998(Hyland, , 2005bPeacock, 2006), attitude markers (Abdi, 2002;Giltrow, 2005), selfmentions (Harwood, 2005a;Hyland, 2001b;Lafuente-Millán, 2010), and engagement markers (Hyland, 2001a(Hyland, , 2002b(Hyland, , 2005b. Taken together, the findings from these cross-disciplinary studies point to disciplinary variation in the use of interactional metadiscourse.…”
Section: Introductionmentioning
confidence: 79%
“…For example, Hyland (2005b) examined interactional metadiscourse in 240 RAs from eight disciplines straddling the hard/soft division and reported that RAs from the soft disciplines used interactional metadiscourse more frequently than RAs from the hard disciplines. Differences between hard and soft disciplines were also reported for specific types of interactional resources: hedges (Abdi, 2002;Hyland, 1998Hyland, , 2005bVold, 2006), boosters (Hyland, 1998(Hyland, , 2005bPeacock, 2006), attitude markers (Abdi, 2002;Giltrow, 2005), selfmentions (Harwood, 2005a;Hyland, 2001b;Lafuente-Millán, 2010), and engagement markers (Hyland, 2001a(Hyland, , 2002b(Hyland, , 2005b. Taken together, the findings from these cross-disciplinary studies point to disciplinary variation in the use of interactional metadiscourse.…”
Section: Introductionmentioning
confidence: 79%
“…There is some agreement in the literature as to the precise linguistic structures that can be used to establish the presence of the readers into the discourse. Following previous studies on this type of metadiscoursal elements (for example Chrismore, Markkanen and Steffensen ; Hyland 2001b; 2002a,b; 2004b; Dafouz ; Hyland and Tse ; Giltrow ) writers can address readers directly using a number of resources including second person pronouns and possessives ( you, your ) and inclusive pronouns and possessives ( we , our , us , one ). In addition, writers can develop a relationship with the readers using asides (direct comments addressed to the reader that are inserted in parentheses), questions, references to shared knowledge or common expectations, and directives.…”
Section: Introductionmentioning
confidence: 99%
“…Būtent tokią vartoseną ir matome pavyzdžiuose (9) ir (10), kuriuose dėmesį patraukia ir kitos įtikinamą autoriaus tekstą kuriančios priemonės: žodžiais dabar, tuojau pat, pradedant nuo pirmadienio primygtinai raginama neatidėlioti autoriaus siūlomo veiksmo (9) pavyzdyje, o (10) apeliuojama į visų be išimties toje srityje dirbančių medikų pareigą atgaivinti Lietuvos visuomenei autoriaus manymu svarbias kūdikių žindymo tradicijas. Apie tokią deontinių modalinių veiksmažodžių pragmatinę vartoseną kalba ir Giltrow (2005): raginimas siekti tų pačių profesinių vertybių tuo pačiu suponuoja ir socialinį bei profesinį autoriaus ir skaitytojo artumą bei tapatumą, o tai yra galinga priemonė kurti įtaigų tekstą.…”
unclassified
“…taisytinus ar keistinus dalykus, pabrėžti perspektyvas ir nurodyti kur link turėtų būti kreipiama mokslinė mintis ir potencialas, kartu parodydami ir savo profesines žinias bei patirtį (žr. Giltrow 2005). Analizuodamas direktyvus, kuriems priskiria ir modalinius veiksmažodžius, Hylandas (2002, 223) pastebi, kad mokslo tiriamuosiuose darbuose jie leidžia autoriui pademonstruoti savo profesinę kompetenciją ir gebėjimą kurti argumentuotą bei įtaigų tekstą.…”
unclassified